A new species of the genus Paraholcostethus Belousova (Hemiptera: Heteroptera: Pentatomidae: Carpocorini) from Korea - Roca-Cusachs, Marcos; Kim, Junggon; Lee, Hodan; Park, Haechul; Jung, Sunghoon (Zootaxa, 2018)
The genus Paraholcostethus Belousova is reported from the Korean Peninsula for the first time with the description of a new species, Paraholcostethus irumiae sp. nov. The generic diagnosis of Paraholcostethus is slightly modified to accommodate the new species. Habitus, male and female internal and external genitalia are illustrated. A key to the species of the genus is also given.